Case Report: A rare case of asymptomatic unroofed coronary sinus in a dog: diagnostic imaging and genetic findings - Choi, Yoonju; Yoon, Wonkyoung; Park, Byung-Yong; Jang, Young-Jin; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2025)
A 2-year-old, 3.8 kg spayed female Pomeranian was presented for a routine health examination with no clinical signs. Physical examination revealed no cardiac murmur. Blood tests were unremarkable and electrocardiography revealed normal sinus rhythm. Thoracic radiography showed a normal cardiac silhouette. Transthoracic echocardiography identified a left atrial size at the upper limit of the normal range (left atrium-to-aortic root ratio: 1.7) and a markedly visualized tubular structure along the posterior wall of the left atrium, presumed to be the coronary sinus. Color Doppler imaging revealed continuous flow into the right atrium without evidence of atrial septal defect. There was no evidence of pulmonary hypertension and a bubble study excluded an intracardiac right-to-left shunt. Subsequent computed tomography identified a 3.6 mm partial defect between the midportion of the coronary sinus and the left atrium, consistent with a partial unroofed coronary sinus. Despite the absence of coronary sinus dilation, contrast enhancement patterns were similar in both the coronary sinus and the left atrium, supporting the presence of a left-to-right shunt. No other congenital abnormalities were identified, and regular follow-up with echocardiography and clinical sign monitoring was recommended. Whole-exome sequencing revealed four unique missense single nucleotide variants in genes potentially implicated in cardiac development. This case highlights that unroofed coronary sinus can occur without clinical signs or associated anomalies in dogs and further presents potential genetic variants identified through whole-exome sequencing, contributing to a better understanding of this rare defect.